Polyomavirus EGFP-pseudocapsids: analysis of model particles for introduction of proteins and peptides into mammalian cells - Boura, E; Liebl, D; Spísek, R; Fric, J; Marek, M; Stokrová, J; Holán, V; Forstová, J (FEBS letters, 2005)
A vector for preparation of mouse polyomavirus capsid-like particles for transfer of foreign peptides or proteins into cells was constructed. Model pseudocapsids carrying EGFP fused with the C-terminal part of the VP3 minor protein (EGFP-VLPs) have been prepared and analysed for their ability to be internalised and processed by mouse cells and to activate mouse and human dendritic cells (DC) in vitro. EGFP-VLPs entered mouse epithelial cells, fibroblasts and human and mouse DC efficiently and were processed by both, lysosomes and proteasomes. Surprisingly, they did not induce upregulation of DC co-stimulation molecules or maturation markers in vitro; however, they did induce interleukin 12 secretion.
Keywords: Humans; genetické vektory; zelené fluorescenční proteiny; proteiny; Microscopy, Electron; dendritické buňky; Proteins; Transduction, Genetic; virion; Green Fluorescent Proteins; interleukin-12; Capsid Proteins; epitelové buňky; lidé; zvířata; myši; transdukce genetická; peptidy; Polyomavirus; Mice; Peptides; Epithelial Cells; Virion; Dendritic Cells; Interleukin-12; virové plášťové proteiny; Genetic Vectors; fibroblasty; elektronová mikroskopie; Animals; Fibroblasts